2015
DOI: 10.1111/iji.12246
|View full text |Cite
|
Sign up to set email alerts
|

Further diversity of the 5′ promoter region of the MHC class I‐related chain B gene

Abstract: We have now found a total of 15 individual MICB promoter sequences, varying by combination of 18 polymorphic positions within the MICB minimal promoter sequence. Sequence-based typing and cloning characterized the three new 5' promoter sequences as MICB-P13, MICB-P14 and MICB-P15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The MICA promoter that is found in association with the vast majority of MICA coding alleles is MICA-P7 and had highest RRR of all promoter types except MICA-P14. MICA-P14 was found uniquely during this study in two individual UCB samples from our cohort of 181 and is described in more detail elsewhere ( 29 ). Transcriptional activity of this promoter is high, around 75% relative to the SV40 control and higher than all other MICA promoters studied.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The MICA promoter that is found in association with the vast majority of MICA coding alleles is MICA-P7 and had highest RRR of all promoter types except MICA-P14. MICA-P14 was found uniquely during this study in two individual UCB samples from our cohort of 181 and is described in more detail elsewhere ( 29 ). Transcriptional activity of this promoter is high, around 75% relative to the SV40 control and higher than all other MICA promoters studied.…”
Section: Resultsmentioning
confidence: 62%
“…Although the population frequency of this promoter type is largely unknown, one study investigating MICA allele and promoter haplotypes suggested an AF for MICA-P6 of around 3% in Chinese Han, on the same haplotype as MICA*008:01 ( 15 ). MICA-P13 and MICA-P14 were identified as a novel promoter types in our cohort of cord blood samples ( 29 ) and have the accession numbers KM358317 and KM358136, respectively. Although we cannot confirm the MICA allele haplotype association with MICA-P14, both individuals with this novel promoter were typed as MICA*008 so it is possible that this allele can be over-expressed in the presence of strong promoters such as P14.…”
Section: Discussionmentioning
confidence: 99%